AN ACOUSTIC ANALYSIS OF THE STRESS ON THE PARTICLE مَا /MAː/ IN QURANIC RECITATION BY NON-ARAB SPEAKERS - Meliyani, Azzah Risti; Al Farisi, Mohamad Zaka; Maulani, Hikmah (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
This study investigates the acoustic stress of the Arabic particle مَا /maː/ in the recitation of the Quran by non-Arabic speakers, focusing on its various grammatical functions. The study highlights the importance of prosody and tajweed in correctly reciting the Quran, emphasizing the nature of stress in conveying the intended meaning of the verses. While there is rich literature on the semantic and syntactic functions of particles in Arabic, phonetic analysis remains largely unexplored. This study uses a qualitative descriptive comparative method by comparing the pronunciation of non-Arab speakers with native speakers. This research aims to provide a deeper insight into the acoustic characteristics of the recitation of the Quran and positively contribute to learning Arabic and the Quran. The findings show that the stress of the particle مَا /maː/ in Surah `Abasa produces some differences between non-Arabic speakers and native speakers. The mismatch between the stress rule on the ما particle and its grammatical function is evidenced by acoustic values that differ from those of native speakers. While these stress differences do not change the meaning of the verse, they do affect the beauty of the Quranic language. The results of this study can also be a reference for further research in acoustic phonetics. In the end, this research is expected to foster a deeper appreciation of the rhythmic beauty of the Quran.